International journal of integrated education Teachers’ Welfare and Motivation: Implications for Students’ Academic Achievement: An Empirical Study - Bolanle Funmilola Adeola; Wakili Hussaina Kyaune; Longsan Ephraim Silas (Researchparks Publishing, 2026)
This study investigated the influence of teachers’ welfare and motivation on students’ academic achievement in public secondary schools in North-central Nigeria. Key welfare indicators examined were salary regularity, promotion opportunities, working conditions, professional development, healthcare benefits and recognition systems. A descriptive survey design was employed. Data were obtained from 420 respondents comprising teachers, principals and students drawn from 15 public secondary schools across North-central Nigeria. The data were analysed using mean scores, standard deviation, Pearson Product-Moment Correlation and Regression Techniques. Findings revealed that teachers’ welfare significantly predicted students’ academic achievement (r =.71, p <.05). Teacher motivation also showed a strong positive relationship with classroom effectiveness and students’ examination performance (r =.68, p <.05). Furthermore, schools with stronger welfare provisions recorded higher student pass rates than schools with weaker welfare systems. The results indicated that teachers who are adequately motivated demonstrate higher commitment, punctuality, better lesson preparation and stronger learner support, all of which positively affect academic outcomes. The study concludes that teacher welfare and motivation remain critical determinants of educational quality and student success in North-central Nigeria. It was therefore recommended that Governments and school Proprietors in the region should prioritise prompt salary payment, timely promotion, housing assistance, healthcare support, continuous professional development and staff recognition schemes in order to strengthen teacher performance and improve students’ academic achievement.